Improvement of wastewater treatment by use of natural coagulants - Prodanović, Jelena; Šćiban, Marina; Antov, Mirjana (Journal of Economic Development, Environment and People, 2013)
An activated sludge and other organic sludges from wastewater treatment processes are usually anaerobically digested prior to application on land. The purpose of digestion is to convert bulky, odorous sludges to relatively inert material that can be rapidly dewatering. The important benefit of this process is a biogas production, too. It is proper to enlarge primary sludge production in a primary settler by adding some coagulation aids, with aim to increase a biogas production, as much as possible. The most common coagulant is alum, but presence of large quantities of aluminum salts in sludge has a harmful impact on digestion and digested sludge application. Some natural coagulants, that have a numerous advantages, can be used instead of alum. Natural coagulants could be extracted from a different plant material, and considering the fact that they are of organic nature, the biogas yield can be enhanced by their presence. A plant material that remains after extraction can be used as a feed. The aim of this paper is a consideration of potential environmental benefits of substitution of alum by natural coagulant extracted from common bean seeds in sewage wastewater treatment process.